ISSUES AND CHALLENGES AMIDST THE PANDEMIC ERA: ENGLISH LEARNERS’ VOICES - Suyansah Swanto; Wardatul Akmam Din; Iziana Hani Ismail; Nur Anneliza Abd Latip (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Corona virus disease 2019 has become a current pandemic and many countries have been affected by it. At the end of January 2020, the WHO Emergency Committee declared a global health emergency state as COVID-19 confirmed cases have been increasing internationally. Since then, online learning has been actively implemented globally including Malaysia. This research is purely qualitative where data was collected via online interview with four willing secondary students. The findings highlight that there are a few weaknesses regarding online learning. Poor internet connection contributes to one of the weaknesses in online learning in Malaysia. Furthermore, not understanding teachersâ€™ teaching is also one of the limitations of online education. Online learning limitations might vary depending on the students’ technological capability to access online sites and use computers. These limitations are more evident for young children or school-age students who may not have online access. Although online learning has its flaws however it comprises several strengths too. Online learning enables the students to have flexible time in participating in the lesson. Avoiding from the virus is the next advantage of conducting online learning. Although schools are closed however students still could get connected with their teachers through several devices like computers, laptops, tablets and mobile phones. Hence, online learning is deemed to be the best alternative to continue the learning process and at the same time protects young learners from this deadly virus.